Aerosol radiative forcing from the 2010 Eyjafjallajökull volcanic eruptions. Issue 15 (6th August 2014) - Flanner, M. G.; Gardner, A. S.; Eckhardt, S.; Stohl, A.; Perket, J.
Abstract Although the 2010 volcanic eruptions of Eyjafjallajökull did not exert a large climate forcing, several features of their emissions favored weaker aerosol cooling or stronger warming than commonly attributed to volcanic events. These features include a high ratio of fine ash to SO2, occurrence near reflective surfaces exposed to strong insolation, and the production of very little stratospheric sulfate. We derive plausible ranges of optical properties and top‐of‐atmosphere direct radiative forcing for aerosol emissions from these events and find that shortwave cooling from sulfate was largely offset by warming from ash deposition to cryospheric surfaces and longwave warming from atmospheric ash and sulfate. Shortwave forcing from atmospheric ash was slightly negative in the global mean under central estimates of optical properties, though this forcing term was uniquely sensitive to the simulated distribution of clouds. The forcing components sum to near climate‐neutral global mean 2010 instantaneous (−1.9 mWm−2) and effective (−0.5 mWm−2) radiative forcing, where the latter is elevated by high efficacy of snow‐deposited ash. Ranges in net instantaneous (−7.3 to +2.8 mWm−2) and effective (−7.2 to +4.9 mWm−2) forcing derived from sensitivity studies are dominated by uncertainty in ash shortwave absorptivity. Forcing from airborne ash decayed quickly, while sulfate forcing persisted for several weeks and ash deposits continued to darken snow and sea ice surfaces for months following the eruption. Despite small global forcing, monthly averaged net forcing exceeded 1 Wm−2 in some regions. These findings indicate that ash can be an important component of climate forcing from high‐latitude volcanic eruptions and in some circumstances may exceed sulfate forcing.